1988
DOI: 10.1126/science.241.4864.438
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation Levels During the Antarctic Spring

Abstract: The decrease in atmospheric ozone over Antarctica during spring implies enhanced levels of ultraviolet (UV) radiation received at the earth's surface. Model calculations show that UV irradiances encountered during the occurrence of an Antarctic "ozone hole" remain less than those typical of a summer solstice at low to middle latitudes. However, the low ozone amounts observed in October 1987 imply biologically effective irradiances for McMurdo Station, Antarctica, that are comparable to or greater than those fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 5 publications
0
53
0
1
Order By: Relevance
“…It has been suggested that the variation in recruitment success for Antarctic benthic invertebrates is on decadal time scales and is caused by variations in current regime, the extension of sea ice cover, or the formation of anchor ice (Dayton 1989;Brey et al 1995;Gutt 2000). During the mid 1980s the annual ''ozone hole'' had already begun to occur with its increase in Austral spring UVB irradiances equivalent to those measured during the Austral summer (Frederick and Snell 1988). The infrequent recruitment events in McMurdo Sound could also be affected by exposure to UVB during springtime ozone depletions, with its potential to cause significant mortality of embryos and larvae in the plankton and further reduce settlement and recruitment to the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the variation in recruitment success for Antarctic benthic invertebrates is on decadal time scales and is caused by variations in current regime, the extension of sea ice cover, or the formation of anchor ice (Dayton 1989;Brey et al 1995;Gutt 2000). During the mid 1980s the annual ''ozone hole'' had already begun to occur with its increase in Austral spring UVB irradiances equivalent to those measured during the Austral summer (Frederick and Snell 1988). The infrequent recruitment events in McMurdo Sound could also be affected by exposure to UVB during springtime ozone depletions, with its potential to cause significant mortality of embryos and larvae in the plankton and further reduce settlement and recruitment to the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…First detected over the Antarctic by Farman et al (1985), seasonal ozone depletion has now also been documented above the Arctic and mid-latitudes (north and south) (e.g. Frederick & Snell 1988, Roy et al 1990, Stolarski et al 1992, Kerr & McElroy 1993. Of immediate concern to this expanding global problem are the potential threats to biological ecosystems (Calkins 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric ozone concentration during spring commonly falls below 50 % and may decline below 30 % of pre-ozone-hole values (Weiler & Penhale 1994). As a result, Antarctic UVB irradiances during spring are at least as high as at the summer solstice (Frederick & Snell 1988). Ozone depletion persists until February (Jones & Shanklin 1995), leading to a 50 to 100% increase in UVB around the summer solstice (Frederick & Lubin 1994).…”
Section: Introductionmentioning
confidence: 99%